2008
DOI: 10.1016/j.jacc.2007.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2C19 681G>A Polymorphism and High On-Clopidogrel Platelet Reactivity Associated With Adverse 1-Year Clinical Outcome of Elective Percutaneous Coronary Intervention With Drug-Eluting or Bare-Metal Stents

Abstract: Patients carrying at least one CYP2C19*2 allele are more prone to high-on clopidogrel platelet reactivity, which is associated with poor clinical outcome after coronary stent placement (Effect of Clopidogrel Loading and Risk of PCI [EXCELSIOR]; NCT00457236).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
351
4
20

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 515 publications
(404 citation statements)
references
References 34 publications
29
351
4
20
Order By: Relevance
“…Concerning the latter, work by Hulot et al [10] has demonstrated the influence of CYP2C19 loss-of-function (LoF) polymorphisms on the biological responsiveness in healthy volunteers. More recently, a paper by Trenk et al, [11] in the Journal of American College of Cardiology, two papers by Simon et al and Mega et al published in the New England Journal of Medicine and one paper in The Lancet by Collet et al confirmed and extended previous reports that the polymorphism of CYP450 2C19 subtypes is an important determinant of responsiveness to clopidogrel and subsequent cardiovascular events [12][13][14]. These observations point to the interest of genotyping patients for whom clopidogrel therapy is indicated.…”
mentioning
confidence: 98%
“…Concerning the latter, work by Hulot et al [10] has demonstrated the influence of CYP2C19 loss-of-function (LoF) polymorphisms on the biological responsiveness in healthy volunteers. More recently, a paper by Trenk et al, [11] in the Journal of American College of Cardiology, two papers by Simon et al and Mega et al published in the New England Journal of Medicine and one paper in The Lancet by Collet et al confirmed and extended previous reports that the polymorphism of CYP450 2C19 subtypes is an important determinant of responsiveness to clopidogrel and subsequent cardiovascular events [12][13][14]. These observations point to the interest of genotyping patients for whom clopidogrel therapy is indicated.…”
mentioning
confidence: 98%
“…5 One of the common causes of individual variations in drug response is genetic polymorphism associated with drug absorption and metabolism. [6][7][8] Clopidogrel is a prodrug that requires active enteric absorption and conversion into an active metabolite in the liver. 9 A key protein involved in clopidogrel absorption is the intestinal efflux transporter P-glycoprotein which is encoded by the ABCB1 gene.…”
mentioning
confidence: 99%
“…Observational studies have demonstrated that a high level of on-clopidogrel platelet aggregation (PA) can result in adverse cardiovascular events after PCI, including stent thrombosis [10][11][12][13] . In this regard, carriers of at least one reduced-function cytochrome P450 2C19 (CYP2C19) allele treated with DAPT have been reported to have low levels of the active metabolites of clopidogrel, diminished platelet inhibition and a high rate of major adverse cardiovascular events among ACS patients undergoing PCI 14) .…”
Section: Platelet Function Testsmentioning
confidence: 99%